The mObywatel App as an Example of Digital Transformation in Public Administration in Poland and the Change in Citizen-State Relations in the Age of the Information Society - Ewa Maria Włodyka; Dorota Sylwia Majewicz (Journal of Modern Science)
Objectives Paper aims to explore how the integration of digital technologies reshapes these interactions within the framework of an information society. The study focuses on evaluating the hypothesis that the mObywatel application, as a pivotal example of digital public administration, catalyzes changes in the interactions between citizens and the state. It will examine the role of digital tools in modifying these relationships and assess the broader implications for civic engagement and administrative efficiency. The research investigate the societal reception of digital transformation initiatives.